2020
DOI: 10.1186/s40246-020-00272-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 preclinical models: human angiotensin-converting enzyme 2 transgenic mice

Abstract: Coronavirus disease 2019 (COVID-19) is a declared pandemic that is spreading all over the world at a dreadfully fast rate. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the pathogen of COVID-19, infects the human body using angiotensin-converting enzyme 2 (ACE2) as a receptor identical to the severe acute respiratory syndrome (SARS) pandemic that occurred in 2002-2003. SARS-CoV-2 has a higher binding affinity to human ACE2 than to that of other species. Animal models that mimic the human diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 127 publications
4
78
0
2
Order By: Relevance
“…As has recently been reported in studies using K18-hACE2 transgenic mice 23,30 , pathology revealed brain involvement in some of the SARS-CoV-2 singly infected and coinfected mice at day 10 which manifested as non-suppurative meningoencephalitis predominantly affecting the midbrain and brainstem. Previous studies using K18-hACE2 mice focusing on SARS-CoV have shown that the virus spreads throughout the brain around 3 days post intranasal inoculation 21,23,31 however the mechanism of entry is unclear as one study reported abundant infection of the olfactory bulb 31 while the other showed little involvement 21 .…”
Section: Discussionsupporting
confidence: 71%
“…As has recently been reported in studies using K18-hACE2 transgenic mice 23,30 , pathology revealed brain involvement in some of the SARS-CoV-2 singly infected and coinfected mice at day 10 which manifested as non-suppurative meningoencephalitis predominantly affecting the midbrain and brainstem. Previous studies using K18-hACE2 mice focusing on SARS-CoV have shown that the virus spreads throughout the brain around 3 days post intranasal inoculation 21,23,31 however the mechanism of entry is unclear as one study reported abundant infection of the olfactory bulb 31 while the other showed little involvement 21 .…”
Section: Discussionsupporting
confidence: 71%
“…Until now, studies based on RBD domain analysis ruled out the probability of mice, rats, and rabbit's involvement in the SARS-CoV-2 cycle [52]. The findings on ferrets, orangutans, and monkeys showed a higher affinity of ACE2 with the RBD domain of SARS-CoV-2 S protein [53].…”
Section: Transmission Of Sars-cov-2 From Covid-19 Positive Persons Tomentioning
confidence: 99%
“…In response to the need for small animal models to study SARS-CoV, several laboratories produced transgenic animals expressing the hACE2 gene under the control of various promotors, including the CMV, HFH4 epithelial cell promotor or the endogenous murine ACE2 promotor (27)(28)(29)(30)(31). Many of these animals develop severe disease upon infection by SARS-CoV, but severity largely depends upon expression levels and tissue distribution of the hACE2 transgene.…”
Section: Introductionmentioning
confidence: 99%